Endovascular treatment of chronic hemoptysis in patients with pulmonary tuberculosis - Loiudice, Giovanni; Catelli, Antonio; Corvino, Antonio; Quarantelli, Mario; Venetucci, Pietro (Acta Biomedica Atenei Parmensis, 2021)
Background: We aimed to demonstrate the safety and efficacy of bronchial artery embolization (BAE) in patients with pulmonary tuberculosis in the planned management of "mild" hemoptysis. This treatment, already widely documented and used as a life-saving therapy in an emergency regimen, if properly planned in poorly controlled patients through medical therapy alone, can provide a valid opportunity by reducing the frequency and extent of non-fatal bleeding, but which still worsen the quality of life of these already significantly traumatized patients. Methods: All procedures were conducted through a right common femoral access with a 5 Fr catheter and a 2.7 Fr super-selective catheter coaxial technique of the branches of the bronchial arteries with suspected bleeding sources. Embolizations were performed with 500-700 micron Terumo PVA plastic microparticles. We decided to adopt the following inclusion criteria for the selection of patients to be enrolled: documented diagnosis of pulmonary TB, the presence of at least one bleeding episode that required at least two blood transfusions, evaluation with bronchoscopic examination to ascertain the bronchial origin of bleeding and the affected lobar site, execution of an angio-ct radiological study for the evaluation of the bronchial systemic anatomy as well as the patency of the pulmonary arterial circulation, general hemodynamic compensation and an age of enrollment between 25 and 65 years. Results: All selective embolization interventions demonstrated a technical success of 100% of the total number of patients. 11 out of 12 patients did not show any signs of relapse or complications related to the interventional procedure at a first check-up carried out at 48 hours, instead a fatal massive hemoptysis occurred in only one patient. At the next three-month follow-up, no relapses were documented in all selected patients. Only one patient required a second embolization four months after the first procedure. Conclusions: Radiological-interventional approach in the elective regimen of super-selective embolization of the bronchial arteries (BAE) in the management and control of "mild" hemoptysis in patients with pulmonary tuberculosis not controlled exclusively by medical therapy, according to a strategy systematic of planned intervention and respecting clear and standardized inclusion criteria, represented in our experience a safe and effective procedure, free from significant short and long term complications, especially in well selected patients, which, although not always allows a definitive and stable control of hemoptysis, can in any case significantly limit the risks, also allowing a better planning of the most appropriate therapeutic intervention strategy.